2019
DOI: 10.1098/rsos.182073
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Couzi et al . (2018): a phenomenological model for structural transitions in incommensurate alkane/urea inclusion compounds

Abstract: This article has been edited by the Royal Society of Chemistry, including the commissioning, peer review process and editorial aspects up to the point of acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…As Toudic et al [2] suggest that our data reported previously [4] for phase II were (in their words) ‘on the wrong phase', they make the further claim that our ‘phenomenological description of the phase behaviour in n -nonadecane/urea is contrary to reliable experimental measurements'. In this Reply, we respond to the issues raised in the Comment of Toudic et al [2].…”
mentioning
confidence: 47%
See 3 more Smart Citations
“…As Toudic et al [2] suggest that our data reported previously [4] for phase II were (in their words) ‘on the wrong phase', they make the further claim that our ‘phenomenological description of the phase behaviour in n -nonadecane/urea is contrary to reliable experimental measurements'. In this Reply, we respond to the issues raised in the Comment of Toudic et al [2].…”
mentioning
confidence: 47%
“…This model is an alternative interpretation to that proposed by Toudic et al . in the work cited in their Comment [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They argue in favor of a single ferroelastic phase transition described in the (a, b) plane [26,44]. We strongly contested this work [45,46]. Here we present high-resolution synchrotron data which prove the originality of the phase transitions when described by taking into account their aperiodic feature by construction.…”
Section: Introductionmentioning
confidence: 59%